Effects of Alignment Between Particle Precipitation and Ion Convection Patterns on Joule Heating. Issue 6 (29th June 2019) - Sheng, Cheng; Deng, Yue; Chen, Yun‐Ju; Heelis, Roderick A.; Huang, Yanshi
Abstract: In the high‐latitude thermosphere and ionosphere the Joule (frictional) heating rate is related to both conductivity and electric field. Thus, an accurate calculation of the Joule heating rate requires self‐consistent specifications of high‐latitude particle precipitation and ion convection patterns. However, general circulation models usually use uncorrelated empirical models to specify high‐latitude particle precipitation and ion convection separately and independently. Here, studies have been conducted to examine the significance of the appropriate spatial alignment of the precipitation and ion convection patterns to the energy input estimation for the upper atmosphere. As shown in Defense Meteorological Satellite Program satellite observations, a close alignment between the particle poleward boundary (PPB) and the convection reversal boundary (CRB) can be identified when the interplanetary magnetic field is strongly southward. To illustrate the importance of this alignment, a comparison between two Global Ionosphere‐Thermosphere Model runs has been conducted. In the first case, the uncorrelated empirical models were used in Global Ionosphere‐Thermosphere Model to specify the high‐latitude electrodynamics. In the second case, the PPB was adjusted to be approximately coincident with the CRB. The alignment between the PPB and the CRB causes changes in the Joule heating distribution and a 50% enhancement of hemispheric integrated Joule heating under extreme conditions. The effect of the alignment on Joule heating and neutral density has also been investigated preliminarily during the 5 August 2011 geomagnetic storm. Key Points: From observations the displacement between the particle and potential patterns is usually within 1–2° when southward B z is dominant The displacement between the convection reversal boundary and the particle boundary from empirical models can be more than 10° After appropriately aligning the particle and potential patterns, the total Joule heating increases up to 50% under extreme conditions